Effects of nasal wall lateralization and pyriform turbinoplasty on nasal air conditioning. Issue 2 (15th December 2016) - Sommer, Fabian; Simmen, Daniel; Briner, Hans Rudolf; Jones, Nick; Hoffmann, Thomas Karl; Scheithauer, Mark Oliver; Lindemann, Jörg
No abstract available